Isolation of antioxidant phenolics from Schinopsis brasiliensis based on a preliminary LC-MS profiling. (August 2017) - Santos, Clisiane Carla de Souza; Masullo, Milena; Cerulli, Antonietta; Mari, Angela; Estevam, Charles Dos Santos; Pizza, Cosimo; Piacente, Sonia
Abstract: The phenolic content of the ethanol extract of the stem bark of the Brazilian plant Schinopsis brasiliensis Engl. (Anacardiaceae) has been evaluated together with the antioxidant activity. The good antioxidant activity exhibited in the Trolox Equivalent Antioxidant Capacity (TEAC) assay (TEAC value = 3.04 mg/mL) encouraged us to investigate its constituents. An analytical approach based on LC-ESIMS n was applied to rapidly obtain a metabolite profile of the ethanol extract of the stem bark of S. brasiliensis . Sixteen phenolic compounds, among which five galloyl derivatives, never reported before, have been isolated and their structures have been unambiguously elucidated by extensive spectroscopic methods, including 1D ( 1 H, 13 C, TOCSY) and 2D (DQF-COSY, HMBC, and HSQC) NMR experiments. Moreover, the antioxidant activity of all the isolated compounds was evaluated, along with the cytotoxicity against the cancer cell lines A549 (human alveolar basal carcinoma) and Hela (human epitheloid cervix carcinoma). The previously undescribed compounds exhibited a high free-radical-scavenging activity, in the range of 1.10–1.86 mM. None of the tested compounds, in a range of concentrations between 12.5 and 100 μM, caused a significant reduction of the cell number. Graphical abstract: An analytical approach based on LC-ESIMS n was applied to obtain a metabolite profile of the ethanol extract of the stem bark of S. brasiliensis (Anacardiaceae) which guided the isolation of five galloyl derivatives (8, 10 –12 and 14 ) never reported before, along with eleven further phenolic compounds. The antioxidant activity, evaluated by TEAC assay and the cytotoxic activity of all isolated compounds were also investigated. Image 1 Highlights: A LC-ESIMS n analysis of the EtOH extract of the stem bark of S. brasiliensis has been performed. Based on the LC-ESIMS n, five previously unreported galloyl derivatives have been isolated and characterized. These compounds exhibited a high free-radical-scavenging activity in the TEAC assay. Isolated compounds did not cause a significant antiproliferative activity against A549 and Hela cancer cell lines.